COMPUTERIZED SYSTEMSGARMENT ORDER ON DATA PROCESSING ON PT. LAXMIDEVI JAYAGARMENT - Dedi Suhatri; Elly Agustina J, SKom, MMSI (Jurnal Sistem Informasi, 2003)
At PT. LAXMIDEVI JAYAGARMENT have difficulty in doing data processing garment orders at his company. The appropriate tools needed to facilitate the conduct data collection incoming orders. Therefore created a computerized system that can help inorder data processing. Usecomputerized order system with the use of computers can be as optimal as possible, especially in the manufacture of scheduled reports and orders more accurately and faster data storage and integrated in a single unit.